Influence of oxidation on steel fiber yarn and knitted fabric properties. (May 2016) - Barburski, Marcin; Lomov, Stepan V
Fine steel fibers are spun into yarns and then knitted into fabric, which is used, among other applications, as a high resistance separation material in forming of automotive glass. In press bending, the glass sheet is first heated to temperature of about 650℃ and subsequently vacuum pressed on a mold covered by steel fiber knitted fabric. This high temperature changes the surface of fibers by oxidation, which influences mechanical properties of yarn and fabrics. The paper investigates interrelation between change of yarn and fabric properties caused by oxidation. Higher tensile resistance of the oxidized fabric corresponds to higher bending stiffness and higher friction of the oxidized yarn. The change of the fabric biaxial tension behavior influences the optical quality of the formed glass.